2023
DOI: 10.3389/fcimb.2023.1257073
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota as a potential biomarker for methamphetamine use disorder: evidence from two independent datasets

Linzi Liu,
Zijing Deng,
Wen Liu
et al.

Abstract: BackgroundMethamphetamine use disorder (MUD) poses a considerable public health threat, and its identification remains challenging due to the subjective nature of the current diagnostic system that relies on self-reported symptoms. Recent studies have suggested that MUD patients may have gut dysbiosis and that gut microbes may be involved in the pathological process of MUD. We aimed to examine gut dysbiosis among MUD patients and generate a machine-learning model utilizing gut microbiota features to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Deep learning models, such as CNNs, allow researchers to identify specific biomarkers from microbial data. This could include microbial communities or gene expression patterns linked to specific toxin exposures (Liu et al, 2023). Microorganism that is stably expressed in different postmortem organs can be used as a biomarker (Javan et al, 2016b), and further, a series of dynamically changing biomarkers can be combined to accurately predict PMI.…”
Section: Application Of Ai In High-throughput Microbiome Data Process...mentioning
confidence: 99%
“…Deep learning models, such as CNNs, allow researchers to identify specific biomarkers from microbial data. This could include microbial communities or gene expression patterns linked to specific toxin exposures (Liu et al, 2023). Microorganism that is stably expressed in different postmortem organs can be used as a biomarker (Javan et al, 2016b), and further, a series of dynamically changing biomarkers can be combined to accurately predict PMI.…”
Section: Application Of Ai In High-throughput Microbiome Data Process...mentioning
confidence: 99%
“…Both compositional and structural alterations of gut microbiota were observed in MA abusers, 26,27 and the alterations were related to psychiatric symptoms and cognitive dysfunctions 27 . Additionally, intestinal microbiota was also suggested to potentially differentiate MA abusers from healthy group 28 . In animal studies, MA exposure was shown to induce gut microbiota dysbiosis, intestinal barrier impairment, neuroinflammation elevation, and behavioral abnormalities 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“… 27 Additionally, intestinal microbiota was also suggested to potentially differentiate MA abusers from healthy group. 28 In animal studies, MA exposure was shown to induce gut microbiota dysbiosis, intestinal barrier impairment, neuroinflammation elevation, and behavioral abnormalities. 29 , 30 However, the neurotoxic effects induced by MA could be ameliorated by optimizing gut homeostasis.…”
Section: Introductionmentioning
confidence: 99%